Sibling Similarities and the Importance of Parental Socioeconomic Position in Electoral Participation - Hannu Lehtinen; Jani Erola; Hanna Wass (My University, 2022)
We studied the impact of an individual’s family and community background on their voting propensity in the 2015 Finnish parliamentary elections by employing a sibling design on an individual-level register-based dataset. The results showed that a quarter of the total variance in voter turnout was shared between siblings. Considering the dichotomous nature of the turnout variable, this implies that background has a strong effect which is almost comparable to sibling similarity in education. Parental socioeconomic position and voting, in turn, are equally important factors by explaining one-third of this shared part of the likelihood of voting. Mothers and fathers make roughly equal contributions. The results suggest that future studies of inter-generational effects in political participation, whenever possible, should use information from both maternal and paternal characteristics and multiple indicators of parental socioeconomic position simultaneously. We conclude by underlining that as people cannot choose their background, voting propensity is strongly influenced by factors beyond an individual’s own control, which is problematic for the functioning of inclusive democracy and equality of opportunity